Hello!

Recall the definitions of tan, csc and cot:

`tan(x)=sin(x)/cos(x),` `csc(x)=1/sin(x), cot(x)=cos(x)/sin(x).`

Therefore the left part is equal to

`sin(x)/cos(x) * 1/(sin^2(x))-sin(x)/cos(x) =sin(x)/cos(x) (1/(sin^2(x))-1)=`

`=sin(x)/cos(x) * (1-sin^2(x))/(sin^2(x)) =sin(x)/cos(x) * (cos^2(x))/(sin^2(x))=cos(x)/sin(x),`

which is really equal to the right part, Q.E.D.

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Hello!

Recall the definitions of tan, csc and cot:

`tan(x)=sin(x)/cos(x),` `csc(x)=1/sin(x), cot(x)=cos(x)/sin(x).`

Therefore the left part is equal to

`sin(x)/cos(x) * 1/(sin^2(x))-sin(x)/cos(x) =sin(x)/cos(x) (1/(sin^2(x))-1)=`

`=sin(x)/cos(x) * (1-sin^2(x))/(sin^2(x)) =sin(x)/cos(x) * (cos^2(x))/(sin^2(x))=cos(x)/sin(x),`

which is really equal to the right part, Q.E.D.